Bootlace lenses for curved arrays - Niazi, Abdullah Y.; Uyguro?lu, Rasime (Publ by IEEE, 1993)
The use of multifocal bootlace lenses as beamforming networks for multibeam array antennas has been well established. The design principles of this lens are introduced and the results of a computer study showing the feasibility of these lenses are presented. The full paper will present results of a study investigating the performance and design parameters of the lens.
Proceedings of the IEEE 1993 International Symposium Digest of Antennas and Propagation --
Keywords: Lenses; Optical communication; Beamforming networks; Lens design parameter; Multifocal bootlace lenses; Antenna arrays